The Application of Detectors in Determining the Safety Intervals at Intersections with Traffic Lights - Perše, Silvestar; Vrhovski, Dražen; Bukljaš, Zdravko (Promet - Traffic&Transportation, 2012)
The paper presents a model of a detector-controlled trafficlight intersection as a complex traffic system. By analysing thekey factors of safety, the preliminary guidelines are given for theimplementation of the presented solution. The special emphasisis on defining the safety intervals as significant safety factorsin passing through an intersection.